Two new species of Plutomurus Yosii (Collembola, Tomoceridae) from the Caucasus - Barjadze, Shalva; Jordana, Rafael; Baquero, Enrique; Giordano, Rosanna; Soto-Adames, Felipe N. (Zootaxa, 2018)
Two new species of Plutomurus, P. pichkhaiai sp. nov. from Garakha and Letsurtsume caves and P. shurubumuensis sp. nov. from Shurubumu Cave (Chkhorotsku district, Western Georgia) are described, and illustrated. The new species are very similar to P. kelasuricus from the Tsebelda karst massif formation in Apkhazeti, Georgia, but differ in having two inner spine-like chaetae on the inner edge of the hind tibiotarsus (only one in P. kelasuricus) and in occupying different, isolated cave formations separated by a geographic distance of nearly a 100 km. A key to the species of Plutomurus with 6 prelabral chaetae is provided.